Engineering mechanics statics - Meriam, J. L. (John Wiley & Sons, 2013)
In the latest edition of Engineering Mechanics, Meriam and Kraige deliver a uniquely powerful learning solution: a sound conceptual foundation for solving mechanics problems that is the hallmark of the Meriam text. The new edition offers easy-to-use tools and resources to drive positive outcomes/success.